Continuous Stirred Tank Reactor: A Process Design for Interesterification of Macauba (Acrocomia aculeata) palm oil - Pedro Prates Valério; Isabella Fonseca Araujo; Juan Canellas Bosch Neto; Jesus Maria Frias Celayeta; Erika Cristina Cren (International Journal of Food Studies)
Other than the edible oils extracted from the Acrocomia aculeata fruit, there is a growing interest in the palm to generate other high value-added products. Relatively high amounts of carotenoids (up to 378 mg kg-1) have been found in the esculent oils mechanically obtained from the fruit mesocarp. From industrial application perspectives, several processes have been proposed to modify native vegetable oils to yield high functional properties of structured lipids. For interesterified products, the thermal effects of industrial reactors are crucial in reaction mechanisms. The present study has taken into account previously estimated kinetic parameters for the overall disappearances of all-trans β-carotene in the Acrocomia aculeata oil (ko= 2.6 x 10-4 min-1; Ea = 105.0003 kJ mol-1; ΔH = 9.8 x 104 J kg-1) to develop a continuous stirred tank reactor (CSTR) kinetic treatment that obeys first-order kinetics. A system of ordinary dierential equations - mass and energy balances - was solved by the 4th order Runge-Kutta method (GNU Octave software). Under research conditions related to interesterification processing (2 h; 393.15 K), the initial concentration of carotenoids (around 11%) showed no significant decrease. Overall, realistic processing effects and conditions have been assessed, integrating results and knowledge, improving prospects of Acrocomia aculeata as a promising source of high-quality raw material, for producing functional ingredients and food with nutraceutical properties.